Efektivitas Media Konkret Papan Dadu Diagram terhadap Hasil Belajar Kognitif Peserta Didik Kelas V SDN Pedurungan Kidul 02 - Rizka Salma Karimah; Noviana Dini Rahmawati; Andy Suyitno; Ngurah Ayu Nyoman Murniati (Journal on Education, 2024)
This research aims to analyze the effectiveness of the concrete media of the dice board diagram on cognitive learning outcomes in grade V students of SDN Pedurungan Kidul 02 Semarang. This study falls into the category of quantitative research using pre-experimental methods. The study's design used One Group Pretest-Posttest. As a research sample, a class VA of 29 students were selected purposively. The data collection methods used are test, documentation, and observation. Data analysis using the Shapiro-Wilk test, t-test, and N-gain test. The results of this study show that the dice board diagram as a concrete media can improve students’ learning outcomes. This is shown by the results of the 0.64 n-gain score test and the 64% n-gain score test percentage showed the category quite effective. Therefore, the diagram's dice board media is effective on the cognitive learning results of students of grade VA SDN Pedurungan Kidul 02